2012
DOI: 10.1186/1471-2229-12-194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salt stress on ion balance and nitrogen metabolism of old and young leaves in rice (Oryza sativa L.)

Abstract: BackgroundIt is well known that salt stress has different effects on old and young tissues. However, it remains largely unexplored whether old and young tissues have different regulatory mechanism during adaptation of plants to salt stress. The aim of this study was to investigate whether salt stress has different effects on the ion balance and nitrogen metabolism in the old and young leaves of rice, and to compare functions of both organs in rice salt tolerance.ResultsRice protected young leaves from ion harm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(121 citation statements)
references
References 19 publications
3
98
0
Order By: Relevance
“…Although, in our study, expression analysis was conducted only in leaves due to difficulties in harvesting root samples, repressed expression of the OsHKT1;5 gene in Juma67 may cause elevated Na + accumulation in the leaves under high salinity conditions. It was reported that down-regulation of the OsHKT1;5 expression may contribute to stimulation of Na + accumulation in old leaves (Wang et al 2012). Taken together with the evidence of the localization of the OsHKT1;5 transcript in aerial parts of rice (Ren et al 2005), repression of the OsHKT1;5 expression may reduce the function of Na + exclusion from shoots.…”
Section: Discussionmentioning
confidence: 51%
“…Although, in our study, expression analysis was conducted only in leaves due to difficulties in harvesting root samples, repressed expression of the OsHKT1;5 gene in Juma67 may cause elevated Na + accumulation in the leaves under high salinity conditions. It was reported that down-regulation of the OsHKT1;5 expression may contribute to stimulation of Na + accumulation in old leaves (Wang et al 2012). Taken together with the evidence of the localization of the OsHKT1;5 transcript in aerial parts of rice (Ren et al 2005), repression of the OsHKT1;5 expression may reduce the function of Na + exclusion from shoots.…”
Section: Discussionmentioning
confidence: 51%
“…Stressed plants kept relatively more nitrogen in the root as compared with nonstressed plants (Fig. 3), probably to support the supply with nitrogen-containing compatible solutes (Wang et al, 2012). Furthermore, enhanced retention of nitrogen compounds in the root might be due to adaptive mechanisms to ensure adequate water and nutrient acquisition from the rhizosphere (Sharp et al, 2004).…”
Section: Integrated Analysis Of Carbon and Nitrogen Metabolismmentioning
confidence: 99%
“…Several studies have suggested that a low cytosolic Na + /K + ratio is required to maintain a favourable ionic homeostasis in plant cells under salinity stress condition [41,42] and that a low Na + /K + ratio improves photosynthesis and overall plant growth [43]. Wang et al [44] reported that under salinity stress, genes related to sodium transport from roots to shoot such as OsHKT1;1, OsHAK10 and OsHAK16 were upregulated in the old leaves of rice. Meanwhile genes involved in facilitating Na + exclusion from root xylem vessels to reduce shoot accumulation, like OsHKT1;5 and OsSOS1, were downregulated, leading to high concentrations of Na + accumulated in old leaves compared to young leaves.…”
Section: Ion Homeostasis and Compartmentationmentioning
confidence: 99%